A Review of Antifungal Resistance in West Africa - Muhindo, Abraham Bwalhuma; Aliero, Adamu Almustapha; Syalhasha, Festo Mwebaze; Ntulume, Ibrahim; Eilu, Emmanuel; Odoki, Martin; Mutebi, Joe (Borneo Journal of Pharmacy, 2024)
Knowledge of local and regional antimicrobial resistance (AMR) is important for clinical decision-making. However, surveillance capacity for fungal infections let alone antifungal resistance is lacking throughout West Africa, and current antifungal resistance data are sparse. We sought to address this gap by summarizing all available high-quality data on antifungal resistance in West Africa. We searched the PubMed database, African Journals Online archives, and free web searches in October and December 2023 using the terms "antifungal resistance" and "West Africa" to find articles published from 2010 onwards. Only 11 articles were included in our analysis most of which were cross-sectional and descriptive in design; relatively high levels of antifungal resistance (AFR) to commonly used antifungals were reported including (24-75%) resistance to fluconazole and ketoconazole, two of the most frequently-prescribed antifungals in this region. There is a high level of resistance to griseofulvin, ketoconazole, cotrimoxazole, and fluconazole among dermatophyte infections (80-100%) with 100% resistance to amphotericin B, ketoconazole, and fluconazole reported by the invasive fungal disease-causing pathogen Cryptococcus neoformans. Resistance to commonly used anti-fungal drugs is prevalent; raising concern that these drugs may no longer be useful for treating moderate or severe fungal infections in West Africa hence calling for countries to promote acceptance of antimicrobial stewardship as a programmatic strategy not just focused on bacterial resistance but also fungal resistance including pharmacy management, laboratory complete mycological investigations and dissemination of standard fungal susceptibility profiles.